Pengembangan Kelas Daring dengan Penerapan Hybrid Learning Menggunakan Chamilo pada Matakuliah Pendidikan Kewarganegaraan - Ary Purmadi; M. Samsul Hadi; Lu'luin Najwa (Universitas Negeri Malang in collaboration with APSTPI and IPTPI, 2018)
The objectives of this study are 1) to develop products from LMS Chamilo that can be used in civic education courses that are suitable for use in learning based on alpha and beta tests. 2) Determine the effectiveness of product use in the citizenship course. The research method used in this research is research and development (R&D). The results of the feasibility of this product are based on the alpha test (alpha test) on the material expert of 3.25 which is included in the